(untitled) (Eurasian Scientific Herald, 2022)
As a result of the work carried out, using the thin-layer chromatography-TLC method, the group composition of oils isolated from some melons was identified, and then their quantitative assessment was carried out. The possibility of using the TLC method for assessing the group composition and authenticity of vegetable oils is shown. Watermelon, melon and pumpkin oils were chosen as vegetable oils. This approach can be used in the standardization of the quality of oils and in the development of regulatory documents for oils.